Gendered financial & nutritional benefits from access to pay-as-you-go LPG for cooking in an informal settlement in Nairobi, Kenya - Matthew Shupler; Jonathan Karl; Mark O'Keefe; Helen Hoka Osiolo; Tash Perros; Willah Nabukwangwa Simiyu; Arthur Gohole; Federico Lorenzetti; Elisa Puzzolo; James Mwitari; Daniel Pope; Emily Nix (World Development Sustainability, 2024)
This study investigates the association between adoption of pay-as-you-go (PAYG) liquefied petroleum gas (LPG), an emerging alternative to full cylinder LPG, and women's economic empowerment in an informal settlement in Nairobi, Kenya. From December 2021-January 2022, 293 customers of a PAYG LPG company (PayGo Energy) were surveyed on their cooking patterns, financial savings and shifts in dietary behaviors following uptake of the technology. Among PayGo Energy customers that previously cooked only with polluting fuels (N = 78; 27 % of customers), daily cooking time was reduced by an average of 42 min/day; 82 % of PayGo Energy customers that previously cooked with full cylinder LPG (N = 216; 73 % of customers) also decreased their cooking time (average of 20 min/day) when switching to PAYG LPG. The majority (58 %; N = 70) of female household heads took on additional employment after switching to PAYG LPG, compared with 36 % (N = 55) of females living in male-headed households. Among female household heads, the proportion of informal sector workers earning wages on an irregular (71 %) or daily basis (61 %) that took on new income-generating activities after transitioning to PAYG LPG was over 20 % higher than those earning monthly salaries (39 %). Increased dietary diversity and consumption of protein-rich foods (legumes, meat, fish) from cooking with PAYG LPG was reported by 15 % of female household heads compared with 5 % of those living in male-headed households. While nearly three-quarters (73 %) of PayGo Energy customers would recommend the service to others because of the added convenience it provides, only one-third (29 %) reported associated health benefits as a key reason for promoting use of PAYG LPG to community members. Female household heads were more likely than non-household heads to be socioeconomically empowered when adopting PAYG LPG, illustrating that women's agency may influence the associated benefits of clean energy transitions. Nonetheless, the time savings reported by nearly all women who switched to PAYG LPG for cooking suggests that promoting the increased convenience of cooking with PAYG LPG may be useful for accelerating its adoption..